2021
DOI: 10.3390/ijerph18094511
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Plantar Fascia and Intrinsic Foot Muscles in a Single-Leg Drop Landing and Repetitive Rebound Jumps: An Ultrasound-Based Study

Abstract: The plantar fascia and intrinsic foot muscles (IFM) modulate foot stiffness. However, it is unclear whether the corresponding ultrasonography findings reflect it. This study aimed to examine the effect of the plantar fascia and IFM morphologies on force attenuation during landing and reactivity when jumping in healthy adults (n=21; age, 21–27 years). Thickness, cross-sectional area (CSA), and hardness of the plantar fascia, abductor hallucis (AbH), and flexor hallucis brevis (FHB) muscles were measured using u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…However, most of the studies have focused on finger or hand-related movement [ 8 , 9 , 24 ]; whether a change in the amount of sensory input can also affect the maximal motor output of the whole-body movement remains to be clarified. Caminita et al showed that cooling-induced decrease in the sensitivity of the soles reduced the squat jump height [ 10 ], but it remains unclear how much of the reduction in the jump height results from the reduction in the sensory input rather than reduction in the dexterity of the plantar fascia and other toe-related muscles whose control is critical in the jumping motion [ 25 , 26 ]. More importantly, although previous studies have focused on decreased maximal motor output due to reduction in the sensory input, an increase in the motor performance under maximum effort due to any sensory input augmentation has been seldom investigated.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of the studies have focused on finger or hand-related movement [ 8 , 9 , 24 ]; whether a change in the amount of sensory input can also affect the maximal motor output of the whole-body movement remains to be clarified. Caminita et al showed that cooling-induced decrease in the sensitivity of the soles reduced the squat jump height [ 10 ], but it remains unclear how much of the reduction in the jump height results from the reduction in the sensory input rather than reduction in the dexterity of the plantar fascia and other toe-related muscles whose control is critical in the jumping motion [ 25 , 26 ]. More importantly, although previous studies have focused on decreased maximal motor output due to reduction in the sensory input, an increase in the motor performance under maximum effort due to any sensory input augmentation has been seldom investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that larger IFMs are related to a high maximum force and contact area of the foot, which are known to be found in foot disorders, such as PF [ 43 ]. Morikawa et al showed that the ultrasonography muscle architecture of the FHB and the plantar fascia were related to the force attenuation in the single-drop jump, and that the AHB and the plantar fascia were related to the repetitive rebound jump test [ 44 ]. These results suggest that changes in the muscles and soft tissues, developed by incorrect biomechanics of the ankle and foot, or heavy load fluctuations, may be observed using USI.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the probe was placed along a line between the third toe and the medial calcaneal tubercle to record the CSA image of the FDB, and was subsequently placed along the same line to record the thickness image (Taş et al, 2020). These measurement methods have been previously reported by our research group (Maeda et al, 2021;Morikawa et al, 2021), and they are reliable in assessing the IFMs thickness and the CSA (Crofts et al, 2014).…”
Section: Evaluation Of Muscle Thickness and Csamentioning
confidence: 93%